2021
DOI: 10.1186/s13099-021-00447-z
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome diversity declines while distinct expansions of Th17, iNKT, and dendritic cell subpopulations emerge after anastomosis surgery

Abstract: Background Anastomotic failure causes morbidity and mortality even in technically correct anastomoses. Initial leaks must be prevented by mucosal reapproximation across the anastomosis. Healing is a concerted effort between intestinal epithelial cells (IECs), immune cells, and commensal bacteria. IEC TLR4 activation and signaling is required for mucosal healing, leading to inflammatory factor release that recruits immune cells to limit bacteria invasion. TLR4 absence leads to mucosal damage fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…These results are in line with what was previously described, where low diversity has been observed in the microbiota of the anastomotic tissue that develops AL [ 27 , 28 , 29 ]. This may be so because reduced diversity may be associated with an increase in undesirable microbiota and a decrease in beneficial microbiota, resulting in compromised intestinal resistance [ 30 ].…”
Section: Resultssupporting
confidence: 93%
“…These results are in line with what was previously described, where low diversity has been observed in the microbiota of the anastomotic tissue that develops AL [ 27 , 28 , 29 ]. This may be so because reduced diversity may be associated with an increase in undesirable microbiota and a decrease in beneficial microbiota, resulting in compromised intestinal resistance [ 30 ].…”
Section: Resultssupporting
confidence: 93%
“…It should be noted that these procedures and, notably, those with caecum suppression, were obviously linked to intestinal insufficiency. It is well known that anatomical reconstructions lead to changes in the physiological function and composition of gut microbiota, including ICR and small bowel SBR, as well as other intestinal surgeries, such as Roux-en-Y gastric bypass procedures [56][57][58]. All may promote a loss of diversity and the deep modification of the microbiota associated with pro-inflammatory events.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in Firmicutes and Bacteroidetes are particularly significant in many pathological states since these two constitute the vast majority of the bacterial population. Trans-differentiation of Th17 cells into regulatory T cells (Tregs) is connected with the ratio of Firmicutes to Bacteroidetes, which could be used as a disease predictor [ 58 ]. Our investigation revealed that the genera Ruminococcaceae_UCG_002 , Holdemanella, Catenibacterium , and Oscillospira , all of the phylum Firmicutes, are associated with the onset of allergic conjunctivitis.…”
Section: Discussionmentioning
confidence: 99%